1998
DOI: 10.1111/j.1432-2277.1998.tb00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diverticulosis and incidence of bowel perforation after kidney transplantation in patients with polycystic kidney disease

Abstract: Sigmoid perforation due to diverticulitis is a life-threatening complication in the postoperative course of allogenic kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
11
0
4
Order By: Relevance
“…Sharp et al reported that patients with ADPKD have no greater risk of diverticular disease (8). Dominguez Fernandez et al supported this opinion (9). Whether diverticulosis itself is peculiar to ADPKD is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Sharp et al reported that patients with ADPKD have no greater risk of diverticular disease (8). Dominguez Fernandez et al supported this opinion (9). Whether diverticulosis itself is peculiar to ADPKD is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…25 Perforation occurs more often in the sigmoid colon but can also occur in the midsigmoid region, cecum, transverse colon, and descending colon. 14,26 A right side colon perforation after renal transplant is rare. 6 Half of the patients in the series reported by Puglisi and associates 25 showed the sigmoid colon as the perforation site.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] Various studies reported that the prevalence of colonic diverticulosis is significantly higher in patients with autosomal dominant polycystic kidney disease (ADPKD) than in the general population or patients on dialysis for other renal diseases. 4,[14][15][16][17][18] Prevalence rates vary from 53.5% to 83%, with the condition attributed to a congenital colonic defect or the secretory action from the renal cysts on the colonic wall. 8 However, the extent of colonic diverticulitis and perforation does not seem to correlate with the primary renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of colon perforations is 1-2% in kidney transplantation patients [10,11]. Diverticulitis is the most common cause [9,12]. Other causes can be ischaemia or CMV colitis [12].…”
Section: Discussionmentioning
confidence: 99%
“…A delay in the diagnosis in patients after transplantation is common, as the symptoms and signs are sparse and often masked by immunosuppression [9]. The incidence of colon perforations is 1-2% in kidney transplantation patients [10,11].…”
Section: Discussionmentioning
confidence: 99%